2018
DOI: 10.3892/ol.2018.8758
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of conversion therapy and its correlation with VEGF expression in unresectable rectal cancer with liver metastasis

Abstract: To investigate the therapeutic effect of conversion therapy and its correlation with vascular endothelial growth factor (VEGF) expression in unresectable rectal cancer with liver metastasis. A total of 116 cases of unresectable rectal cancer patients with liver metastasis were randomly divided into control and observation group, 58 cases in each group, all of these patients were treated by conversion therapy, patients in control were treated by FOLFOXIRI treatment program, and in observation group were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…While including anti-VGFR therapy such as Bmab in chemotherapy regimens was introduced to exhibit significant benefits on OS in the ARTIST trial [ 38 ], the treatment effect on OS was not reported in other trials [ 17 , 25 , 34 , 57 ]. A previous NMA reported consistent findings of comparable OS and AEs grade ≥3 for FOLFOX/FOLFIRI/FOLFOXIRI/CAPEOX plus Bmab vs. chemotherapy alone, although FOLFOX/FOLFIRI plus Bmab resulted in a significantly better disease control rate and PFS than did FOLFOX/FOLFIRI [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While including anti-VGFR therapy such as Bmab in chemotherapy regimens was introduced to exhibit significant benefits on OS in the ARTIST trial [ 38 ], the treatment effect on OS was not reported in other trials [ 17 , 25 , 34 , 57 ]. A previous NMA reported consistent findings of comparable OS and AEs grade ≥3 for FOLFOX/FOLFIRI/FOLFOXIRI/CAPEOX plus Bmab vs. chemotherapy alone, although FOLFOX/FOLFIRI plus Bmab resulted in a significantly better disease control rate and PFS than did FOLFOX/FOLFIRI [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…OS was defined as the time frame from randomization to death or the last date that the patient was known to be alive for those not known to have died, whichever occurred first [ 12 ]. As a result, a total of 49 studies from 45 RCTs were included in the final analysis [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%